Comparison Between Davidson-Cole and Frequency-Band Limited Fractional Differentiator I/O Type Transfer Function with Speed and Acceleration Inputs in Path Tracking Design - Yousfi, N.; Melchior, P.; Rekik, C.; Derbel, N.; Oustaloup, A. (Journal of Applied Nonlinear Dynamics, 2026)
A new approach to path tracking design based on fractional prefilter was developed in this paper. In path tracking design, the dynamic of actuators must be taken into account in order to reduce over- shoots appearing for small displacements. Taking into consideration the maximum velocity, acceleration, jerk, and the bandwidth of the closed-loop on which the input is applied, it permits the generation of an optimal movement reference-input giving a minimum path comple- tion time. An approach to path tracking based on fractional prefilter has been developed. This approach based on a Davidson-Cole (DC) and Frequency Band Limited Fractional Differentiator (FBLFD) pre- filters, with position input. This work describes an extension of this method. It consists of a path tracking using fractional differentiation and comparison between different types of prefilters by direct opti- mization of an Input/Output (I/O) transfer function with speed and acceleration inputs. Fractional differentiation has been used through a Davidson-Cole and frequency band-limited fractional differentiator (FBLFD) prefilters. A simulation on a motor model validates the developed methodology.